2013
DOI: 10.4103/0300-1652.119602
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of diabetes and its associated ocular manifestations by diabetic patients: A study at Korle-Bu Teaching Hospital, Ghana

Abstract: Background:Diabetes mellitus is a significant cause of visual impairment, hence adequate knowledge on this condition and its ocular manifestations is of immense importance to diabetic patients.Aim:To assess the knowledge of diabetic patients on the disorder and its ocular manifestations, and their attitude towards ocular examinations.Materials and Methods:A cross-sectional survey involving the use of a structured interview was conducted among diabetic patients attending the Diabetic Clinic of the Korle-Bu Teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 17 publications
3
46
5
2
Order By: Relevance
“…Despite higher awareness of diabetic retinopathy that could lead to blindness among diabetic patients in Kano Nigeria, only 15.7% of then ever had an eye check up (Mohammed & Waziri, 2009). It was also demonstrated that some of the diabetes patients had no or lower knowledge with regards to regular eye check up and the frequencies of follow up (Ovenseri-Ogbomo et al, 2013;Shetgar et al, 2015;Thapa et al, 2012). They did not know that eye examination is essential to those who own diabetic.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite higher awareness of diabetic retinopathy that could lead to blindness among diabetic patients in Kano Nigeria, only 15.7% of then ever had an eye check up (Mohammed & Waziri, 2009). It was also demonstrated that some of the diabetes patients had no or lower knowledge with regards to regular eye check up and the frequencies of follow up (Ovenseri-Ogbomo et al, 2013;Shetgar et al, 2015;Thapa et al, 2012). They did not know that eye examination is essential to those who own diabetic.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of diabetic retinopathy was also related with the attitude to seek for an eye check up (Ovenseri-Ogbomo et al, 2013). The age of the patients especially those among 35 to 50 years were associated with the awareness of diabetic retinopathy (Addoor, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations